Affine Algebraic Geometry 2013
DOI: 10.1142/9789814436700_0016
|View full text |Cite
|
Sign up to set email alerts
|

Invariant hypersurfaces of endomorphisms of the projective 3-space

Abstract: We consider surjective endomorphisms f of degree > 1 on the projective n-space P n with n = 3, and f −1 -stable hypersurfaces V . We show that V is a hyperplane (i.e., deg(V ) = 1) but with four possible exceptions; it is conjectured that deg(V ) = 1 for any n ≥ 2; cf. [7], [3].Dedicated to Prof. Miyanishi on the occasion of his 70th birthday

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…and Höring proved that no irreducible hypersurface of P n of degree n is totally invariant (see [Hör17]). This last statement finishes the proof of the conjecture in P 3 thanks to Zhang who showed that no quadric of P 3 is totally invariant (see [Zha13,Thm 1.1.]). Our goal here is to prove the two following theorems.…”
Section: Introductionsupporting
confidence: 52%
“…and Höring proved that no irreducible hypersurface of P n of degree n is totally invariant (see [Hör17]). This last statement finishes the proof of the conjecture in P 3 thanks to Zhang who showed that no quadric of P 3 is totally invariant (see [Zha13,Thm 1.1.]). Our goal here is to prove the two following theorems.…”
Section: Introductionsupporting
confidence: 52%
“…Remark 1.8 and Example 1.10). In Corollary 1.4, X is indeed a Fano manifold; but one would like to know more about the V and even expects X = P n and V be a hyperplane; see [30] and the references therein. Such an expectation is very hard to prove even in dimension three and proving the smoothness of V is the key, hence the relevance of Proposition 2.1 below.…”
Section: Introductionmentioning
confidence: 99%